2009
DOI: 10.1016/j.nbd.2008.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of wild-type human APP in mice causes cognitive deficits and pathological features unrelated to Aβ levels

Abstract: Transgenic mice expressing mutant human amyloid precursor protein (APP) develop an age-dependent amyloid pathology and memory deficits, but no overt neuronal loss. Here, in mice overexpressing wild-type human APP (hAPP wt ) we found an early memory impairment, particularly in the water maze and to a lesser extent in the object recognition task, but β-amyloid peptide (Aβ 42 ) was barely detectable in the hippocampus. In these mice, hAPP processing was basically non-amyloidogenic, with high levels of APP carboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
90
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(100 citation statements)
references
References 60 publications
(59 reference statements)
9
90
1
Order By: Relevance
“…Our previous study is in agreement with others showing that full length WT AβPP can induce apoptosis in the human SH-SY5Y neuroblastoma and differentiated NBP2 neuroblastoma cell lines [17,18]. Furthermore, an in vivo study using WT AβPP overexpressing mice showed that these mice develop memory deficits independently of Aβ accumulation in the hippocampus [19]. Collectively, the above studies suggest that full length AβPP may contribute to AD pathogenesis; however, whether its localization to mitochondria is necessary to induce neuronal cell death is currently unknown.…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our previous study is in agreement with others showing that full length WT AβPP can induce apoptosis in the human SH-SY5Y neuroblastoma and differentiated NBP2 neuroblastoma cell lines [17,18]. Furthermore, an in vivo study using WT AβPP overexpressing mice showed that these mice develop memory deficits independently of Aβ accumulation in the hippocampus [19]. Collectively, the above studies suggest that full length AβPP may contribute to AD pathogenesis; however, whether its localization to mitochondria is necessary to induce neuronal cell death is currently unknown.…”
Section: Introductionsupporting
confidence: 92%
“…While it has been well documented that Aβ fragments induce cell death both in vitro and in vivo, there is emerging evidence that AβPP and its intracellular domain (AICD) may also contribute to AD pathogenesis [16][17][18][19]27,28]. In this study, the overexpression of AβPP in a mouse hippocampal cell line induced a caspase-dependent and Bax-mediated apoptotic pathway which appeared to be largely independent of AβPP processing.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…A large amount of Aβ was found to be generated in cell lines of tau hyperphosphorylation, which could not be clearly explained by the amyloid cascade hypothesis (Fukumoto et al, 2002). In addition, another report showed that in mice overexpressing wild-type human amyloid precursor protein (APP), memory deficits and increasing levels of phosphorylated tau occurred early, whereas Aβ was not detected, which supported the view of an Aβ-independent pathogenic pathway in AD (Simón et al, 2009). Other studies have indicated that tau phosphorylation plays an important role in AD pathology (Oddo et al, 2006;Roberson et al, 2007).…”
Section: Introductionmentioning
confidence: 96%